OPTIMIZATION OF PROGESTERONE 11?-HYDROXYLATION IN THE PRESENCE OF ?-CYCLODEXTRIN (Biological Sciences - PJSIR, 2004)
Aspergillus ochraceus NRRL 405 was used to hydroxylate progesterone to 11a-hydroxyprogesterone (11a-HP). This study described the effect of some fermentation parameters and the intermittent addition of b-cyclodextrin on the biocon- version process. The Kinaway’s medium with pH 6 produced the best result of the used culture media. The transformation period was 48 h for the maximum hydroxylation. The maximum production of 11a-HP (93.10%) was obtained by the addition of 4g/I b-cyclodextrin at 12 h after inoculation compared to the control culture (56.8%). The results also showed the ability of the mould culture to carry out the transformation reaction at high substrate levels without by products formation in the presence of b-cyclodextrin